A novel algorithm for longitudinal track-bridge interactions considering loading history and using a verified mechanical model of fasteners. (15th March 2019) - Luo, Jun; Zeng, Zhiping
Highlights: A longitudinal resistance model of fasteners considering loading history is proposed. The proposed model is validated by an experiment. A novel nonlinear numerical algorithm for the track-bridge interaction is derived. Abstract: The mechanical behavior of fasteners has considerable influence on track–bridge interaction (TBI) analysis, and a consensus has been gradually reached that their loading history and nonlinear characteristics should be taken into account. In this study, we present a new variation pattern of the longitudinal resistance of the fasteners considering loading history, which was experimentally verified based on the Dahl friction model. The model's mechanical behavior was more consistent with measured results compared with previously proposed Ruge's model and the double-spring model. According to the new model, an algorithm for TBI analysis considering loading history was derived based on the Ritz method and the principle of minimum potential energy, which was applied in a case study of an N -span, simply-supported girder bridge in a high-speed railway with a typical loading sequence: (1) the seasonal temperature change of the bridge; (2) the bending of the bridge structure under a vertical train load; (3) the braking of the train. Additionally, some significant conclusions were obtained by comparing the numerical results and adopting the mechanical parameters of the fasteners specified in various codes, according to both the linear superposition method (LSM) and loading history method (LHM).